(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Stomatal distribution is found to be an important trait of rice cultivars for increasing yield. A total of six rice cultivars, three from each of inbred and hybrid cultivars, were used to study stomatal distribution on the leaf epidermis and its influence on yield and yield attributing characters of rice during the Boro season. The hybrid cultivars exhibited superiority in respect of number of stomata, length and breadth of stomatal apparatus. They also produced longer panicle, higher number of filled grains panicle1, heavier grains and finally, higher grain yield ha1 than inbreds. The higher grain yield of the hybrid cultivars might be due to higher number of large sized stomata causing higher photosynthetic efficacy, although, they produced relatively lower number of effective tillers hill1. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18207 J. Bangladesh Agril. Univ. 11(1): 47-52, 2013